Mind Over Mouth: Psychological Determinants of Oral Health – A Review - Woźniak, Martyna; Słomianny, Marcela; Kutnik, Karolina; Kusibab, Karolina; Sikora, Gabriela; Czechowski, Michał; Skórska, Gabriela; Koguc, Karolina; Kolada, Karolina; Sajda, Małgorzata (Journal of Education, Health and Sport, 2025)
Background: Mental health conditions such as stress, depression, anxiety, and eating disorders can significantly influence oral health. These psychological factors affect oral function, behavior, and quality of life, yet their role in overall health remains underrecognized. Aim: To review current literature on the psychological determinants of oral health and examine their broader implications for individual and population well-being. Methods: A narrative review was conducted using 39 peer-reviewed articles identified through PubMed, Scopus, and Google Scholar. The studies were organized into five thematic categories: stress-related symptoms, depression-associated neglect, dental anxiety, eating disorders, and psychosomatic manifestations. Results: Psychological disorders were associated with bruxism, xerostomia, dental erosion, chronic oral pain, and decreased oral health-related quality of life. Mental distress often led to harmful behaviors and neglect of self-care. Psychosomatic conditions presented diagnostic challenges. Interdisciplinary strategies, including psychological and physiotherapeutic interventions, were shown to enhance health outcomes. Integrating mental health support into oral and general health frameworks appears essential for effective prevention and intervention. Further research is needed to establish standardized approaches for identifying and managing psychological influences on oral health. Conclusions: Oral health and mental well-being are closely interconnected and should be considered together in health promotion and disease prevention strategies. A holistic understanding of health requires integration of psychological, behavioral, and somatic dimensions.